PERENCANAAN GEDUNG PERKULIAHAN BERTINGKAT MENGGUNAKAN BETON BERTULANG BERDASARKAN SNI 2019 DI KABUPATEN BEKASI - Atthariq Sihabudin Suhrawardi; Herol; Isria Miharti Maherni Putri; Juse Roejanto (Jurnal Pelita Teknologi, 2025)
Bekasi Regency, in addition to being one of the largest industrial cities in Indonesia, is also an area that is experiencing rapid population growth and economic development in supporting various needs, including educational facilities. The purpose of this design is to produce a design for a multi-storey lecture building using reinforced concrete according to environmental conditions in Bekasi Regency through the Special Moment Resisting Frame System (SRPMK) approach. With a design method based on SNI 2019, structural modeling using the SAP2000 program, and analyzing the reinforcement plan using Microsoft Excel. Thus, the results of the analysis show that the structural elements of the planned building can withstand various forces with shifts that are still within safe limits. In understanding building design, it plays an important role, so that the application of multi-storey buildings on former rice fields such as in Bekasi Regency can be applied, therefore it is hoped that this design can be a reference for related government agencies and readers and further researchers.